-4-6(6m-2)=-64

Simple and best practice solution for -4-6(6m-2)=-64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-6(6m-2)=-64 equation:


Simplifying
-4 + -6(6m + -2) = -64

Reorder the terms:
-4 + -6(-2 + 6m) = -64
-4 + (-2 * -6 + 6m * -6) = -64
-4 + (12 + -36m) = -64

Combine like terms: -4 + 12 = 8
8 + -36m = -64

Solving
8 + -36m = -64

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -36m = -64 + -8

Combine like terms: 8 + -8 = 0
0 + -36m = -64 + -8
-36m = -64 + -8

Combine like terms: -64 + -8 = -72
-36m = -72

Divide each side by '-36'.
m = 2

Simplifying
m = 2

See similar equations:

| 2.39=m(3.29)+0.59 | | -2x-8x=4-8x | | 5x-(8-x)=4a-10 | | 5p-2p=54 | | 1.3x-4.42=x-2.5 | | 4w+2w=48 | | (-1.59)(-0.5)= | | 240=lwh | | 0.50x+0.45(30)=47.5 | | 2(x+12)+4=28 | | 13=26y | | 3x-7y=-23 | | -59.78=4.9(n-6.4) | | -11.1=w/6+8.1 | | 6=-2m-3(4m+5) | | 20+8x=10+10y | | 141+3x=564 | | 8=34x-60 | | -4+3n-4n=n-2 | | y/3=7.5 | | 2y=4y-3 | | x+0.8=x+0.2 | | c=39.08+0.50 | | 21+14r+35t= | | X+20=410 | | f(-5)=4x-x^2 | | 3v+8-4-14=-3+2v | | w-1/2=-3/4 | | 35X+2y=90 | | -4(1+6n)=-76 | | -3(2x-7)=12 | | v-2.4=7.75 |

Equations solver categories